Constraining maximum event magnitude during injection-triggered seismicity - Ziyan Li (Nature Portfolio, 2021)
Recently triggered seismic events such as the Pohang earthquake have exceeded predictions of average energy releases by a factor of 1000. A new framework is proposed to define maximum event magnitudes as a function of pre-existing critical stresses and fluid injection volume.